1991
DOI: 10.1029/90tc02132
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in PB isotopic compositions of feldspars in plutonic rocks of the northern Appalachian Mountains, U.S.A., and Canada: A geochemical method of terrane correlation

Abstract: Feldspar Pb isotopic compositions from Paleozoic tonalitic to leucogranitic Caledonian plutons from the northern Appalachian Mountains of the U.S.A. and Canada range from nonradiogenic to radiogenic relative to the evolution curve of Stacey and Kramers (1975). Pb isotopic values in the feldspars are generally independent of modal and major and trace element contents of the plutons. Plutons with the least radiogenic Pb isotopic signatures (Northern group) have intruded allochthonous rocks closest to the North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 65 publications
7
56
0
Order By: Relevance
“…6, data from twelve plutons in our study area correspond quite closely with the field of results determined for plutonic rocks in the Central Maine province of Ayuso (1986). Ayuso (1986) and Ayuso and Bevier (1991) suggested that the isotopic ratios in the Central Maine province are the result of mixing of lead from Grenville-type (%1.0-1.2 Ga) basement (their Northern Maine group) and Avalonian-type (%0.60-0.65 Ga) basement (their Coastal Maine group). We suggest, however, that their data for the Central Maine province results from mixing of lead in sedimentary aprons that spread oceanward from peri-Laurentian (including Grenville) and peri-Avalonian terranes, rather than from the actual basements.…”
Section: Contributions Of Common Lead Datasupporting
confidence: 64%
See 3 more Smart Citations
“…6, data from twelve plutons in our study area correspond quite closely with the field of results determined for plutonic rocks in the Central Maine province of Ayuso (1986). Ayuso (1986) and Ayuso and Bevier (1991) suggested that the isotopic ratios in the Central Maine province are the result of mixing of lead from Grenville-type (%1.0-1.2 Ga) basement (their Northern Maine group) and Avalonian-type (%0.60-0.65 Ga) basement (their Coastal Maine group). We suggest, however, that their data for the Central Maine province results from mixing of lead in sedimentary aprons that spread oceanward from peri-Laurentian (including Grenville) and peri-Avalonian terranes, rather than from the actual basements.…”
Section: Contributions Of Common Lead Datasupporting
confidence: 64%
“…This approach works well in regions, such as northern New Brunswick, where VMS and plutonic feldspars both yield strongly radiogenic leads that are characteristic of the underlying Gander terrane and of Avalon and associated terranes (Slack et al, 1991;Ayuso and Bevier, 1991). In northern New Hampshire, however, VMS and plutonic feldspar Pb isotope compositions do not agree.…”
Section: Contributions Of Common Lead Datamentioning
confidence: 96%
See 2 more Smart Citations
“…Also, shown are isotopic fields for the Grenville (Vermont, Ontario, and Cape Breton Island). Sources of data include: Ayuso and Bevier (1991), R.A. Ayuso and N. Ratcliffe (unpub. data), DeWolffe and Mezger (1994), Ayuso et al (1996), and Whalen et al (1997, and references therein).…”
Section: Grenville Massifs Peri-gondwanan Terranes and The Slate Bementioning
confidence: 99%